Experiencing Cerebrovascular Diseases like Stroke and Fear of Falling: Longitudinal Results from the Survey of Health, Ageing and Retirement in Europe - Agon Tahiraj; Hans-Helmut König; André Hajek (Geriatrics, 2024)
Objective: The aim of this study was to clarify the link between experiencing cerebrovascular diseases (strokes as an explicit example) and fear of falling (FOF) among middle-aged and older adults in Europe. Methods: Longitudinal data were used from wave 5 to wave 7 of the representative Survey of Health, Ageing and Retirement in Europe (SHARE). Self-reported tools were used to quantify the key variables. Fear of falling was similarly assessed using a dichotomous yes or no question, “For the past six months at least, have you been bothered by any of the health conditions on this card”, with fear of falling being one of the options. It was adjusted for various sociodemographic and health-related factors. In particular, to account for unobserved heterogeneity, conditional fixed effect regressions (FE) were used. Accordingly, change in an individual’s FOF status over the included waves was analysed and correlated with the reported change of all the included time-varying independent variables within the same individual, including experiencing stroke or other cerebrovascular diseases. The final analytical sample equalled n = 22.071 observations. Results: Conditional logistic FE regressions showed that the onset of a stroke or other forms of cerebrovascular disease was not associated with an increased likelihood of experiencing fear of falling (OR = 1.25, p = 0.095). However, stratified by sex, such an association was present in men (OR = 1.79, p = 0.006), though not in women (OR = 0.94, p = 0.732). Conclusions: The onset of a stroke or other cerebrovascular diseases was associated with an increased likelihood of experiencing FOF in men but not women. Efforts are required to assist older men in avoiding FOF after the onset of stroke or other cerebrovascular pathologies.